If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5x * 2 = 33 Reorder the terms for easier multiplication: 4x + -5 * 2x = 33 Multiply -5 * 2 4x + -10x = 33 Combine like terms: 4x + -10x = -6x -6x = 33 Solving -6x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = -5.5 Simplifying x = -5.5
| 3(c-2)-3=-15 | | 4x+2=5y+1 | | -3x-x+3=-5 | | 10x+7.5y=420 | | 8x-17=5x+13 | | h=-36t^2+gt+d | | y-8=-6(x+1) | | 4eX=20 | | 7x+2y+4=9+11y-x | | 5*4+20= | | -15=y+82 | | 4x^2-19x-52=0 | | -9=w-13 | | 2(x-9)=7 | | 7x+10=10x+7 | | 8=y+14 | | 2.7x+142=3571 | | 5*21+20+8*21-100= | | 2.7x+142=7000 | | 8+4s=-16 | | x^2+2x-400=0 | | y=(x-3)(x-9) | | 7+2y=y | | -8v-3=5v^2 | | 8x^3(9x^2-6x+8)= | | 6u-w=u-4w | | 3x-4y=16ni | | 35=(2w+3)w | | 6-6x=5-2x-64-4x | | 10x^2+88x=88 | | 7x+9y=142506 | | -7(-3+6d)-(2-6h)(-6)= |